2020
DOI: 10.1111/hsc.13067
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in the long‐term impact of the economic recession on preventive healthcare use and health‐related lifestyle in Spain (2006–2017)

Abstract: Spain is one of the European countries in which the economic recession of 2008 has had the strongest impact. The economic recession implied an exponential increase in unemployment, a real estate crisis, a decrease in Gross Domestic Product and a budget deficit for regional governments. The deleterious effects of the economic recession on population health have previously been documented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Inequalities were operationalised in terms of education, income/wealth, social class, or job type. Low SEP individuals consistently had greater decreases in fruit and vegetable intake [46,54,55,58,60,65,70] while patterns of meat and fish consumption were less clear but generally suggestive of inequalities [30,58,65,69]. Results were more mixed for fast food consumption [36,60].…”
Section: Inequalitiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Inequalities were operationalised in terms of education, income/wealth, social class, or job type. Low SEP individuals consistently had greater decreases in fruit and vegetable intake [46,54,55,58,60,65,70] while patterns of meat and fish consumption were less clear but generally suggestive of inequalities [30,58,65,69]. Results were more mixed for fast food consumption [36,60].…”
Section: Inequalitiesmentioning
confidence: 93%
“…Thirty-four studies reported on food intake, generally located in high and middle income countries [30-37, 39, 41, 42, 45-47, 49-52, 54-62, 64-70]. The most common outcome was consumption of a food group or an amount of food as a binary outcome per day/ week [37,41,55,56,58,59,65,69,70]. Other commonly used outcome measures included expenditure or frequency of consumption in a specified time period [33,36,45,47,52,54,60,61,[66][67][68] or share of calories or calorie intake from food groups [31,32,39,49,51,52].…”
Section: Food Intakementioning
confidence: 99%
See 3 more Smart Citations